Study on Internal Timber Demand Supply Ratio in Community Forest Users’ Groups of Middle Mountain Region of Nepal - Sapkota, Bishwa Bandhu; Bhattarai, Kisman; Rimal, Simant (International Journal of Environment, 2018)
Higher internal timber demand compared to the supply capacity of forest has been attributing to scarcity of timber within Community Forest Users’ Groups (CFUGs) and subsequently posing risk to the sustainability of forest. It is therefore becoming crucial to examine the factors behind such high demand to supply ratio and quantify their relationship to help in optimum allocation of forest resources to the community. In this study, we selected potential variables that could affect the internal demand-supply (DS) ratio in a community forest users’ groups, examined their correlation with it, and develop a parsimonious model that could explain the relationship between them using linear regression technique and Akaike Information Criterion methodology. The correlation coefficient analysis showed that household density (0.75) had very strong relationship whereas other predictor variables such as, growing stock per hectare (0.35), percentage of households involved in agriculture (0.37), area of forest (-0.39), percentage of timber yielding species in a forest (-0.56), and percentage of rich household (0.62) in a CFUG had weak to fair relationship with DS ratio. Among the four different models designed with the top three highly correlating variables, the third model utilizing household density and percentage of timber yielding species proved to be most parsimonious model. The developed linear model is of high relevance for forest officials in rational and scientific formation of community forest users’ group and handover of forest resources to such groups. International Journal of Environment Volume-6, Issue-4, Sep-Nov 2017, page: 42-55